Chemical Compound Profile of Infusion from Crescentia cujete Fruit Peel and Toxicity Test against Artemia sallina Leach - Rahma Diyan Martha; Maya Sri Ashira; Choirul Huda; Danar Danar (Biology, Medicine, & Natural Product Chemistry, 2026)
Cancer is one of the top causes of death around the world, thus we need to make safer and more selective anticancer drugs from natural sources. The objective of this work is to identify the chemical constituents and evaluate the toxicity of infusions derived from the fruit peel of Crescentia cujete L., a potential bioactive candidate. Samples were botanically identified, prepared as infusions using a water-heating method (1:10 w/v), then concentrated and analysed by phytochemical screening, LC–MS, and the Brine Shrimp Lethality Test (BSLT) on Artemia salina larvae at concentrations of 25–2000 ppm. Screening results showed the presence of alkaloids, flavonoids, saponins, and tannins The LC-MS analysis showed 105 compounds, and the main alkaloid was marmeline (m/z 351.1834). The BSLT test resulted in an LC50 of 187.15 ppm, indicating moderate toxicity and potential for bioactivity or cytotoxicity. The correlation between alkaloid dominance and the LC50 value suggests that the C. cujete fruit peel infusion has potential for further development as a source of natural-based anticancer compound candidates.